DIFFERENCE QUANTITY SLEEP, BLOOD PRESSURE AND LEVEL NOREPINEPHRINE IN PREGNANT WOMAN WITH SEVERAL PREECLAMPSIA WHO GETTING CONSERVATIVE TREATMENT IN VIP WARDS AND ORDINARY WARDS - Kotarumalos, Sitti Sarifah (Journal Nursing Care and Biomolecular, 2018)
Introduction: Pregnancy with severe preeclampsia characterized by hypertension often experience sleep disturbance and quantity. This pathology is compounded by activation of the sympathetic nervous system and possibly by stress associated with resting patterns. One of the management of severe preeclampsia is conservative treatment. The success of conservative care is influenced by the quantity factor of sleep in hospitalized patients. The inpatient room is one of the most important physical facilities for the patient care and healing. Method: Using a cohort study design, conducted on 30 pregnant women with severe preeclampsia. The sample was divided into two groups: 15 mothers were treated in the VIP wards and 15 mothers in ordinary wards. Instruments for collecting sleep duration was using question sheet, norepinephrine levels in 24-hour urine test that performed on the first-day treatment and before pregnancy termination (post-treatment). Data analysis using independent t-test. Result and analysis: In this research, normality test is done by using Shapiro-Wilk test. The decision criteria, namely when the value of Sig or p-value greater than the level of significance = 0.05. The results showed a significant mean difference (p = <0.005) between sleeping duration in VIP wards that is 7,1556Â±35337 hours which was higher than the duration of ordinary wards 5,9921Â±1,02829 hours. While the results of post-treatment blood pressure and post-treatment norepinephrine levels showed no significant difference (p = >0.005) Discussion: the difference of patient care in VIP wards and ordinary wards can affect the sleep disturbance and quantity. Enough sleep for 7 hours during pregnancy can avoid stressful conditions which can increase the production of adrenal hormones that one of the causes in elevated blood pressureÂ